Prevalence of Lumpy Skin Disease in Africa: A Systematic Review and Meta-Analysis from 2007 to 2023 - Balemual Abebaw (Veterinary Medicine International)
Background. Lumpy skin disease (LSD) is an economically important, transboundary viral disease of cattle caused by LSD virus. This systematic review and meta-analysis are concerned with summarizing the status of lumpy skin disease in Africa. Methods. Literature searches between 2007 and 2023 were conducted using different database searches: Google, Google Scholar, PubMed, and Science Direct, and then the required information were extracted. A random effect model was used to pool estimates of prevalence at 95% CI. Publication bias was assessed by applying funnel plots. Results. The pooled estimated prevalence of LSD was 54% (95% CI: −0.09–1.18), with individual study prevalence ranging from 6 to 89%. Subgroup analysis showed that the random pooled prevalence of LSD was 28% (95% CI: −1.48–2.03) in Ethiopia, 37% (95% CI: −3.79–4.52) in Uganda, 88% (95% CI: −0.11–1.28) in Zimbabwe, and 58% (95% CI: −6.96–8.72) in Egypt. No single study was documented from western and northern Africa. Conclusion. The estimated pooled LSD prevalence was investigated as high and indicated nonsignificant variation among study countries. Thus, vaccination of cattle, quarantine, and biting insect control should be applied to control the disease.